Highly potent human hematopoietic stem cells first emerge in the intraembryonic aorta-gonad-mesonephros region - Ivanovs, Andrejs; Rybtsov, Stanislav; Welch, Lindsey; Anderson, Richard A; Turner, Marc L; Medvinsky, Alexander (The Journal of experimental medicine, 2011)
Hematopoietic stem cells (HSCs) emerge during embryogenesis and maintain hematopoiesis in the adult organism. Little is known about the embryonic development of human HSCs. We demonstrate that human HSCs emerge first in the aorta-gonad-mesonephros (AGM) region, specifically in the dorsal aorta, and only later appear in the yolk sac, liver, and placenta. AGM region cells transplanted into immunodeficient mice provide long-term high level multilineage hematopoietic repopulation. Human AGM region HSCs, although present in low numbers, exhibit a very high self-renewal potential. A single HSC derived from the AGM region generates at least 300 daughter HSCs in primary recipients, which disseminate throughout the entire recipient bone marrow and are retransplantable. These findings highlight the vast regenerative potential of the earliest human HSCs and set a new standard for in vitro generation of HSCs from pluripotent stem cells for the purpose of regenerative medicine.